Music as a (Science as a) Liberal Art at Princeton - Aaron Girard (Zeitschrift der Gesellschaft für Musiktheorie)
The influence of ‘scientific’ methodology and discourse on the design of Princeton University’s research programs in music theory and composition has often been asserted, but never adequately defended or contextualized. The literature on this subject has suffered from several flaws: an over-emphasis on Milton Babbitt at the expense of his colleagues; a conflation of distinct paradigms of scientific research; a near-total absence of documentary research; and a disquieting elision of the polemical with the historiographical. This paper, based on archival sources, argues for a decentering of Babbitt and for a new emphasis on the influence of Princeton’s institutional history. With the rejection of conventional wisdom, the ‘scientific’ nature of theory and composition at Princeton becomes clearer: a revisionist history is then required, to facilitate more detailed analysis and to prevent the casual ingress of unsubstantiated opinions.